2014
DOI: 10.1386/jdsp.6.2.205_1
|View full text |Cite
|
Sign up to set email alerts
|

Contact improvisation, the non-eroticized touch in an ‘art-sport’

Abstract: This article is from the first chapter of a Ph.D. thesis and introduces some pivotal experiences and emerging beliefs that inspired the past two decades of professional practice, incorporating contact improvisation (CI), Body-Mind Centering® (BMC®) and Dance Movement Psychotherapy (DMP). The purpose of this article is to indicate the epistemology of my professional self, a touch specialist, presented in three emerging roles: the CI practitioner/teacher, the BMC practitioner/teacher and the DMP practitioner/tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…Sociology and cultural studies have identified touch as a vital medium of human communication, while also acknowledging it as a strictly regulated behavior governed by culturally specific norms (Manning 2007; Guru 2017; Sarukkai 2009; Classen 2005). Scholarship on the use of CI within movement therapy, as a mode of rehabilitation within community practices, also echoes its healing and generative properties (Houston 2009; Dymoke 2014). However, although its healing, generative, and connective properties have been celebrated in dance studies, there is still an unmet need to identify and examine choreographic touch, especially as it shapes CI, as a discriminatory practice, through the intersectional lenses of race, caste, and gender politics.…”
Section: Unmaking Contact (Improvisation)mentioning
confidence: 99%
“…Sociology and cultural studies have identified touch as a vital medium of human communication, while also acknowledging it as a strictly regulated behavior governed by culturally specific norms (Manning 2007; Guru 2017; Sarukkai 2009; Classen 2005). Scholarship on the use of CI within movement therapy, as a mode of rehabilitation within community practices, also echoes its healing and generative properties (Houston 2009; Dymoke 2014). However, although its healing, generative, and connective properties have been celebrated in dance studies, there is still an unmet need to identify and examine choreographic touch, especially as it shapes CI, as a discriminatory practice, through the intersectional lenses of race, caste, and gender politics.…”
Section: Unmaking Contact (Improvisation)mentioning
confidence: 99%
“…More crucially, I observed the lack of physical contact with others (Dymoke, ; Paxton & Kilcoyne, ). When provided with an opportunity to move with others, using contact improvisation and physical theatre techniques, unsurprisingly these issues were addressed (Dymoke, , ). In touring with deaf blind, deaf and disabled performers we embodied the potential for inclusion in the arts and society, each one of us experiencing a subjective and communal sense of breaking with taboo and the conceived norm.…”
Section: Context—touch Reveals Its Absencementioning
confidence: 99%
“…I recall the unconscious/conscious dialogues in our embodied therapeutic relationship, referred to above; in touching me Sarah is being touched deeply. Like a membrane her touch is a locus of meeting self and other—a membrane for communication, for an expression of a desire for support and a means to sense and feel herself in relationship to another (Dymoke, , ). At this place she is able to sense her corporeality as a unity, contained and enlivened.…”
Section: Theoretical Underpinning and Clinical Outcomesmentioning
confidence: 99%
“…Reconociendo que la cultura sexual es performada de forma heterogénea de acuerdo con las particularidades interseccionales de clase, raza/etnicidad, género, edad, religión, etc., las sexualidades se configuran como un "archipiélago extendido y difuso de modos erráticos de encuentro, negociación y disfrute" (Elizalde y Felitti, 2015: 10), en tanto experimentos sociales cotidianos (Giddens, 1998). Es así como en numerosas prácticas artísticas encontramos configuraciones particulares de las sexualidades y los erotismos, como sucede en la danza contact improvisación (Dymoke, 2014;Sciurano, Martínez Albanesi y Nardacchione, 2021) y los clubs electrónicos (Blázquez, 2012;Lenarduzzi, 2012Lenarduzzi, y 2014, donde se performan políticas sexuales particulares.…”
Section: Introductionunclassified
“…La mayoría de los estudios consultados relacionan el erotismo a la sexualidad (Bianciotti, 2015;Carozzi, 2015;Dymoke, 2014;Hanna, 2010;Liska, 2018;Markowitz, 2003;Vionnet, 2020), y solo en algunos casos lo vinculan a la fuerza creativa (Esteban, 2020) y/o a la intensidad vital y sensorial (Esteban, 2020;Lenarduzzi, 2012Lenarduzzi, y 2014. Respecto de esta última forma de organización del erotismo, Lenarduzzi (2012 y 2014) propone el concepto de pista de baile pos-sexual para analizar el mundo de la música electrónica de Buenos Aires, donde se presenta una erótica ampliada, "una suerte de «amor oceánico» que nos invade quizá tanto como el «enamoramiento» […] pero su «erotismo» no es específicamente sexual" (Lenarduzzi, 2012: 273).…”
Section: Introductionunclassified